Impact of climate change on some grapevine varieties grown in Peru for Pisco production - Yzarra Tito, Wilfredo Julián (2015)
The Peruvian region of Ica is an important area ofgrapevine cultivation, mainly for the production of pisco, the flagship hard drink of Peru. The effects of a changing climate have been assessed using the recorded temperatures of a weather station together with projected climates for the 21st century generated under the A1B SRES scenario.